Investigating physical parameters potentially associated with mass coral bleaching events in the Coral Triangle - Peñaflor, Eileen L.
The rising temperature of the ocean, together with the frequent occurence of thermal anomalies, has become one f the major concerns.Intense anomalies in sea temperatures have resulted in coral bleaching occurrences, and even led to coral mortality in various parts of the world. This study investigates the patterns in the timing and extent of anomalies of some parameters associated with coral bleaching occurrences in the Coral Triangle. These parameters include sea surface temperature (SST), wind speed, cloudiness, and photosynthetically active radiation (PAR). Investigation of the Intertropical Convergence Zone (ITCZ) latitude position is also included since this parameter is said to be affected by El Niño Southern Oscillation (ENSO) and might provide additional insight to the process that favors coral bleaching occurrence.